Evaluation of Substance Use Disorder Readmission and Length of Hospital Stay in a Major Rehabilitation Center in the Gulf States: a Retrospective Cohort Study. - Ramadan, Majed; Alharbi, Aysha; Ahmad, Rami Ghazi; Alkhalaf, Ahmed; Alhusseini, Noara; Algarni, Alanood S.; Mohamed, Izzeldin Siddig (International Journal of Mental Health & Addiction, 2024)
Substance use disorders (SUDs) patients have longer lengths of hospital stay, and more unplanned readmissions than other hospitalized patients. We aim to evaluate SUD-related rehospitalization and length of hospital stay in a major rehabilitation center that serves countries of the Gulf States. In a retrospective cohort study for 16-year data set in Al-Amal Hospital Electronic Health Record in the city of Dammam, Eastern region of Saudi Arabia, patients received services from the SUD treatment programs in the period of January 1, 2005, to December 31, 2021. We used cause-specific Cox proportional hazards regression model to estimate risk of readmission, and general linear model to examine the association between substance use disorders and length of hospital stay. Of the total cohort, 4398 (30.17%) were readmitted within 1 year of discharge date. More than half of the cohort were unemployed patients (52.93%). Patients diagnosed with amphetamine use disorder were 1.36 higher risk of readmission compared to no amphetamine disorder (HR = 1.36; CI (1.04, 1.78) P.02). Patients diagnosed with mental disorder had 7.25 times higher risk of longer hospital stay compared to no mental health disorder (coefficient = 7.25; P <.0001). Amphetamine use disorder increased the risk of readmission. A secondary diagnosis of mental disorders among SUD patients increased length of hospital stay. As a targeted region of amphetamine smuggling in the world, policy and clinical decision-makers in Saudi Arabia and the Gulf States should consider taking proactive steps to minimize the future anticipated high demand for addiction treatment in the region.